2016
DOI: 10.1073/pnas.1522014113
|View full text |Cite
|
Sign up to set email alerts
|

Retinal neurodegeneration may precede microvascular changes characteristic of diabetic retinopathy in diabetes mellitus

Abstract: Diabetic retinopathy (DR) has long been recognized as a microvasculopathy, but retinal diabetic neuropathy (RDN), characterized by inner retinal neurodegeneration, also occurs in people with diabetes mellitus (DM). We report that in 45 people with DM and no to minimal DR there was significant, progressive loss of the nerve fiber layer (NFL) (0.25 μm/y) and the ganglion cell (GC)/inner plexiform layer (0.29 μm/y) on optical coherence tomography analysis (OCT) over a 4-y period, independent of glycated hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
471
7
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 511 publications
(514 citation statements)
references
References 57 publications
30
471
7
6
Order By: Relevance
“…9 Different studies using SDOCT have reported a decrease in RNFL and GCL/IPL thickness in diabetic patients without DR. [30][31][32] Sohn and associates quantified the decrease in the inner retinal layer thickness over time in 45 diabetic patients with or without mild nonproliferative DR and reported a progressive decrease in RNFL of 0.25 mm/year and in GCL/IPL of 0.29 mm/year over a period of 4 years, regardless of HbA1c, age, or sex. 33 Interestingly, in this study the variable retinopathy was negatively associated with the overall RT (central, S3, T3, I3, and N3 sectors), ONL (T6 and I6 sectors), and PR layer (N6 sector). In the span of just 1 year, the presence of DR decreased the overall RT in the studied locations between 13.04 and 16.63 mm.…”
Section: This Longitudinal Study Of 125 Type 2 Diabeticmentioning
confidence: 41%
“…9 Different studies using SDOCT have reported a decrease in RNFL and GCL/IPL thickness in diabetic patients without DR. [30][31][32] Sohn and associates quantified the decrease in the inner retinal layer thickness over time in 45 diabetic patients with or without mild nonproliferative DR and reported a progressive decrease in RNFL of 0.25 mm/year and in GCL/IPL of 0.29 mm/year over a period of 4 years, regardless of HbA1c, age, or sex. 33 Interestingly, in this study the variable retinopathy was negatively associated with the overall RT (central, S3, T3, I3, and N3 sectors), ONL (T6 and I6 sectors), and PR layer (N6 sector). In the span of just 1 year, the presence of DR decreased the overall RT in the studied locations between 13.04 and 16.63 mm.…”
Section: This Longitudinal Study Of 125 Type 2 Diabeticmentioning
confidence: 41%
“…Photoreceptor degeneration in this condition promotes vasoregression. Given the role of the neurovascular unit in disease development and progression, it would be interesting to discover which comes first in the diabetic retina-vasoregression or neuronal degeneration [70]. Although most studies have suggested that vascular changes occur first, recent observations suggest the opposite.…”
Section: Models With Retinal Degeneration: Lessons For the Diabetic Rmentioning
confidence: 99%
“…1998; Sohn et al. 2016), and apoptosis may be one of the mechanisms contributing to neuroretinal tissue loss in diabetes. Thereby, triggered retinal neurodegeneration may also participate in the development of early microvascular changes occurring in DR such as the breakdown of the blood–retina barrier, vasoregression and neurovascular coupling impairment (Simó & Hernández 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2015; Sohn et al. 2016). Using optical coherence tomography (OCT), subtle atrophic changes in retinal thickness could be detected non‐invasively in diabetic patients with early retinopathy and to a lesser extent also in patients without retinopathy (Biallosterski et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation